Investigation of inductive coupling approach for non-contact bidirectional transfer of power and signal - Arshad, Atika; Khan, Sheroz; Alam, A. H. M. Zahirul; Tasnim, Rumana (2012)
Powering implantable low wattage biomedical devices and sensors through non-contact means is on the rise over the past recent years. In view of that, inductive coupling is currently the most favorable means of transferring energy for powering the low wattage implanted devices. The wireless inductive link works as an energy link to power up remote devices and also acts as a communication link to retrieve and write data to the same remote device by using the same set of inductive coils. This paper proposes an op-amp based inductive coupling circuit in order to analyze the magnetic coupling of two coils which can be applicable for the activation of microwatt electronic implants. The inductive powering system is incorporated with an op-amp circuit connected with an inductive sensor constructed by a receiver (embodied by the secondary winding of transformer), a transmitter coil (represented by the primary winding of transformer) and a monitoring device. Moreover this paper also discusses on some design considerations of the inductive power link and evaluates the work mathematically using MATLAB.